Participation and empowerment as emancipatory praxis: an ethnographic study of an NGO in Chiapas, Mexico. Issue 5 (4th July 2022) - Mason, Garland; Niewolny, Kim L.
ABSTRACT: Despite a robust legacy of scholarship that has critiqued participation in development, the relationship between participation and empowerment remains unclear. Adelanto is a small non governmental organisation in Chiapas, Mexico, engaged in radical participatory community development. Using an ethnographic approach, we examined Adelanto's politicised participatory approach, analysing assumptions that attempt to link radical participation with empowerment. Our findings illustrate Adelanto's commitment to a participatory approach defined by solidarity as critical to their success in advancing participant self-mobilisation. These results represent new insight into linkages between participation, empowerment, and emancipation by demonstrating the centrality of downward accountability within localised development praxis.